The Algorithm of Change (Journal of Parents and Teachers, 2018)
The main objective of this article is to show our school change experience. It starts just as a methodological transformation about how we teach maths and then step by step it turns into a bigger transformation that involves other subjects and even the own school way of organising, the whole educational community takes part in this experience making a global change experience.
Keywords: maths; learning; discovery learning; pedagogical innovation; educational community; school change; active maths; family participation; teacher participation